Effect of magnetic field on the free-convection and mass transfer flow through a porous medium - Jha B.K.; Prasad R. (My University, 2025)
An analytical study is performed to examine the effects of magnetic field on the free-convection and mass transfer flow through porous medium. The effects of various parameters on the velocity field are discussed by tables. © 1989 Kluwer Academic Publishers.